2017
DOI: 10.1021/acs.chemrev.6b00746
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of Semiconductor Surfaces for Molecular Electronics

Abstract: Inserting molecular monolayers within metal/semiconductor interfaces provides one of the most powerful expressions of how minute chemical modifications can affect electronic devices. This topic also has direct importance for technology as it can help improve the efficiency of a variety of electronic devices such as solar cells, LEDs, sensors, and possible future bioelectronic ones. The review covers the main aspects of using chemistry to control the various aspects of interface electrostatics, such as passivat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
206
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(212 citation statements)
references
References 243 publications
3
206
0
3
Order By: Relevance
“…The bottom-up surfacef unctionalization [1][2][3][4][5][6] has attracted considerable attention in the development of functional thin films and materials for aw ide range of interdisciplinary applications including molecular electronics, [7][8][9][10] electrochromism, [11] information storage, [12] sensors, [13] logic circuits, [14] andm olecular switches. [15][16][17][18][19] In this context, the chemistry of surface modification by self-assembled or -adsorbed monolayers (SAMs) and layer-by-layer (LBL) growth of multilayersi sh ighly promising to construct two-dimensional( 2D) and even three-dimensional (3D) chemical systemso ns urfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The bottom-up surfacef unctionalization [1][2][3][4][5][6] has attracted considerable attention in the development of functional thin films and materials for aw ide range of interdisciplinary applications including molecular electronics, [7][8][9][10] electrochromism, [11] information storage, [12] sensors, [13] logic circuits, [14] andm olecular switches. [15][16][17][18][19] In this context, the chemistry of surface modification by self-assembled or -adsorbed monolayers (SAMs) and layer-by-layer (LBL) growth of multilayersi sh ighly promising to construct two-dimensional( 2D) and even three-dimensional (3D) chemical systemso ns urfaces.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the photocatalytic materials are mainly inorganic semiconductors, such as TiO 2 , ZnO, and CdS . Their application in real life is greatly limited, due to their low light conversion efficiency and the difficulty in structural modification . It is necessary to develop new types of photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…[59][60][61][62] Their application in real life is greatly limited, due to their low light conversion efficiency [63][64][65] and the difficulty in structural modification. [66][67][68] It is necessary to develop new types of photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…From the aspect of underlying mechanisms, it is found that the interactions between surface metal cations of semiconductor colloids and coordination atoms or ions (S, P, N, halide ions, etc.) of ligands affect significantly the interfacial electronic processes, including the defect passivation, band structures and Fermi levels, carrier concentration and conduction type as well as electron/hole mobility . For instance, the surface replacement of long‐chain organic surfactants with small inorganic ligands enables to greatly enhance the carrier mobility and (photo)electronic performance of semiconductor colloids (especially lead chalcogenides) ,.…”
Section: Introductionmentioning
confidence: 99%
“…of ligands affect significantly the interfacial electronic processes, including the defect passivation, band structures and Fermi levels, carrier concentration and conduction type as well as electron/hole mobility. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] For instance, the surface replacement of longchain organic surfactants with small inorganic ligands enables to greatly enhance the carrier mobility and (photo)electronic performance of semiconductor colloids (especially lead chalcogenides). [4][5][6][7][9][10][11] The band edge energies and the p-or n-type conduction of PbS QDs can be adjustable by altering the surface ligands of different intrinsic dipole moment.…”
Section: Introductionmentioning
confidence: 99%